Inorganic Metal Oxide Nanocrystal Photocatalysts for Solar Fuel Generation from Water - Townsend, Troy K.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
Troy Townsend's thesis explores the structure, energetics and activity of three inorganic nanocrystal photocatalysts. The goal of this work is to investigate the potential of metal oxide nanocrystals for application in photocatalytic water splitting, which could one day provide us with clean hydrogen fuel derived from water and solar energy. Specifically, Townsend's work addresses the effects of co-catalyst addition to niobium oxide nanotubes for photocatalytic water reduction to hydrogen, and the first use of iron oxide 'rust' in nanocrystal suspensions for oxygen production. In addition, Townsend studies a nickel/oxide-strontium titanate nanocomposite which can be described as one of only four nanoscale water splitting photocatalysts. He also examines the charge transport for this system. Overall, this collection of studies brings relevance to the design of inorganic nanomaterials for photocatalytic water splitting while introducing new directions for solar energy conversion.
Keywords: Chemistry; Renewable energy resources; Inorganic chemistry; Catalysis; Renewable energy sources; Alternate energy sources; Green energy industries; Chemistry; Inorganic Chemistry; Catalysis; Renewable and Green Energy; Electronic books